Perception of Guardians on the Use of Artificial Intelligence in Educational Geometry Games for Children - Estevam, Leonardo; Melo, Vitor; Carvalho, João; Silva, Barbara da; Oliveira Júnior, Walter; Mota, Marcelle; Lisboa, Diego; Seruffo, Marcos (Anais da Brazilian Conference on Intelligent Systems (BRACIS); 2025: Anais da XXXV Brazilian Conference on Intelligent Systems, 2025)
The study aims to evaluate caregivers’ perceptions of the use of Artificial Intelligence (AI) in educational games for children, emphasizing the positive impact of this technology on the learning process. The research, conducted with 14 caregivers, utilized a comprehensive questionnaire to collect feedback on various aspects, such as the level of engagement fostered in children, the appropriateness and variety of the proposed activities, and the quality of AI-generated questions. The results revealed a positive response to the game, with a satisfaction rate of 93.4%, and indicated that most participants found the use of AI both engaging and enjoyable, highlighting the games’ ability to capture children’s attention in a meaningful way. Furthermore, the majority of caregivers rated the AI-generated questions as appropriate and diverse, considering the content well-suited to children’s educational needs. This assessment demonstrates the effectiveness of AI in providing an interactive and personalized geometry learning experience, allowing each child to progress at their own pace in an engaging manner aligned with their comprehension levels. This adaptive learning approach, which adjusts content according to each child’s progress, was widely recognized by caregivers as an important advancement for educational development, delivering a high-quality, engaging, and educational experience.